On the wake dynamics of a propeller operating in drift - Di Mascio, A.; Muscari, R.; Dubbioso, G. (Journal of fluid mechanics, 2014)
The onset and the nature of dynamic instabilities experienced by the wake of a marine propeller set in oblique flow are investigated by means of detached eddy simulations. In particular, the destabilization process is inspected by a systematic comparison of the wake morphology of a propeller operating in pure axisymmetric flow and in drift with angle of 20°, under different loading conditions. The wake behaviour in oblique flow shows a markedly different character with respect to the axisymmetric condition: in the latter, the destabilization is triggered by an increasing interaction of the main vorticity confined in the tip vortex; whereas, in the former, the role of the secondary vorticity (oriented in the streamwise direction) as well as the hub vortex seems to be crucial. The features of the wake have been investigated by the $\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let ≤ =\leqslant \let \ge =\geqslant \let ≥ =\geqslant \def \Pr {Pr}\def \Fr {Fr}\def \Rey {Re}λ _{2}$ criterion (Jeong & Hussain, J. Fluid Mech., vol. 285, 1995, pp. 69–94) and typical flow variables (pressure, velocity and vorticity), for both the averaged and instantaneous flow fields. Moreover, in order to further inspect the evolution of the vortical structures, as well as their interaction and destabilization, the spectra of the kinetic energy have been considered. This investigation aims to broaden the knowledge from previous works on the subject of rotor wake instabilities, focusing on the differences between an ideal (axisymmetric) and actual operating conditions occurring in typical engineering applications.